2022
DOI: 10.3389/fgene.2022.995644
|View full text |Cite
|
Sign up to set email alerts
|

Development of an exosome-related and immune microenvironment prognostic signature in colon adenocarcinoma

Abstract: Background: The correlation between exosomes and the tumor immune microenvironment has been proved to affect tumorigenesis and progression of colon adenocarcinoma (COAD). However, it remained unclear whether exosomes had an impact on the prognostic indications of COAD patients.Methods: Expression of exosome-related genes (ERGs) and clinical data were downloaded from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) database. The ERGs associated with prognosis were identified and exosome-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Some studies have suggested that HOXC6 is associated with immune dysfunction. In colon adenocarcinoma, a predictive hallmark according to the presence of CCKBR, HOXC6 , and POU4F1 was discovered to be actively related to immune activity, microsatellite instability, gene expression of immune checkpoints, and poor sensitivity to chemotherapy [ 49 ]. This study was based on the TCGA and Gene Expression Omnibus (GEO) databases for bioinformatics analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that HOXC6 is associated with immune dysfunction. In colon adenocarcinoma, a predictive hallmark according to the presence of CCKBR, HOXC6 , and POU4F1 was discovered to be actively related to immune activity, microsatellite instability, gene expression of immune checkpoints, and poor sensitivity to chemotherapy [ 49 ]. This study was based on the TCGA and Gene Expression Omnibus (GEO) databases for bioinformatics analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, POU4F1, which paired with miR-150-5p, was a neuro transcription factor that was closely related to AML1/ETO gene fusion in acute myeloid leukemia ( Dunne et al, 2010 ). It might affect the prognosis of patients with COAD through exosomes and the tumor immune microenvironment ( Cui et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that exosomes mediate crosstalk between immune cells and MSI/MSS CRC, and participate in the regulation of CRC immune status and function in the TME 149 . Cui et al 150 identified three exosome-related genes (ERGs) as key prognostic genes in CRC patients through bioinformatics analysis and confirmed that these ERGs were highly expressed in multiple CRC cells. Cui et al 150 calculated risk scores for CRC patients based on the coefficients of these ERGs and divided patients into high- and low-risk groups.…”
Section: Immunoregulatory Role Of Exosomes In the Crc Microenvironmentmentioning
confidence: 95%
“…Cui et al 150 identified three exosome-related genes (ERGs) as key prognostic genes in CRC patients through bioinformatics analysis and confirmed that these ERGs were highly expressed in multiple CRC cells. Cui et al 150 calculated risk scores for CRC patients based on the coefficients of these ERGs and divided patients into high- and low-risk groups. Further analysis revealed that the levels of resting CD4 memory T cells, resting dendritic cells, and activated dendritic cells were higher in patients with low-risk scores, while the level of activated NK cells was higher in patients with a high-risk score.…”
Section: Immunoregulatory Role Of Exosomes In the Crc Microenvironmentmentioning
confidence: 95%